Adaptive Neuro-Controller for three axes attitude control of innovative satellite - Siti Maryam Sharun; Mohd Yusof Mashor, Prof. Dr.; M. N. Norhayati; W. N. Hadani; Sazali Yaacob, Prof. Dr. (Science Academy, 2011)
Link to publisher's homepage at www.sciacademypublisher.com